Drug rash with eosinophilia and systemic symptoms syndrome in an elderly man on carbamazepine – A jeopardising clinical entity - George, Alna Merin; Khader, Abdul; CS, Sarojiniamma (Indian Journal of Case Reports, 2024)
Drug rash with eosinophilia and systemic symptoms syndrome (DRESS) is a rare but serious hypersensitivity drug reaction most frequently associated with antiepileptics. We report a case of carbamazepine-induced DRESS syndrome in a 61-year-old man who was recently initiated on carbamazepine (6 weeks back) and presented with a history of acute febrile illness of 10 days duration. General examination showed multiple erythematous coalescent papules and rash over the body with relative sparing of the face with lymphadenopathy. Laboratory results revealed eosinophilia, atypical lymphocytosis, transaminitis, and negative serology for hepatitis. Registry of severe cutaneous adverse reactions (RegiSCAR) scoring system case is categorized as a definite case with a score of 7. Carbamazepine was discontinued and with the initiation of intravenous steroids; the transaminitis improved, fever and rashes resolved. We report a case of carbamazepine induced DRESS syndrome in a 61-year-old man. He was recently initiated on carbamazepine (6 weeks back), who presented to with a history of acute febrile illness of 10 days duration. General examination showed multiple erythematous coalescent papule and rash over the body with relative sparing of face with lymphadenopathy. Laboratory results revealed an eosinophilia, atypical lymphocytosis, transaminitis and negative serology for hepatitis. RegiSCAR scoring system was used our case is categorized as definite case with a score of 7. Carbamazepine was discontinued and with initiation of intravenous steroids; the transaminitis improved, fever and rashes resolved.